Enhancing Organizational Commitment Through Work Experience: The Mediating Role of Job Satisfaction - Fidela Hanan Zivana; Wahyuddin Bagenda; Yani Restiani Widjaja (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the effect of work experience on organizational commitment, the effect of work experience on job satisfaction, the effect of job satisfaction on organizational commitment, and the effect of work experience on organizational commitment through job satisfaction as a mediating variable in employees of RS X in Semarang. The method used was a quantitative approach with a correlational research design, using questionnaires as a data collection instrument, involving 86 respondents selected through simple random sampling techniques, and analyzed using classical assumption tests, multiple linear regression, and Sobel mediation tests. The results showed that work experience had a significant effect on organizational commitment, as shown by a significance value of 0.001 which was smaller than 0.05. Work experience has also been shown to have a significant effect on job satisfaction with a significance value of 0.000. Other findings show that job satisfaction has a significant effect on organizational commitment, with a significance value of 0.023. The mediation test showed that job satisfaction was able to mediate the influence of work experience on organizational commitment, where the indirect influence coefficient was proven to be significant based on the results of the Sobel test. Overall, this study confirms that employees' work experience not only shapes job satisfaction, but also strengthens their attachment to the organization, both directly and through the role of job satisfaction mediator.